Revitalisasi Kepemimpinan Pendidikan Perempuan Dalam Perspektif Islam - Pramitha, Devi (J-PAI: Jurnal Pendidikan Agama Islam, 2015)
Nowadays, women’s leadership became a public issue that is always discussed and has provoked polemics and debates between the pros and cons. Women’s capacity to be a leader has always been the main things questioned by various groups when women’s leadership discourse develops in public, especially when the debate is linked to the Islamic perspective. Whereas, the mission of Islam is to free human beings, both of men and women from the shackles of oppression, backwardness and injustice. In education, Goldring and Chen (1994) reported that women in the UnitedKingdom and wherever most women only take part in the teaching profession, but there are relatively few and far who have important positions authorities in a number of secondary schools, colleges and local administration education. Whereas, the result of the study conductedJirasinghe and Lyons, (1996) describe the personality of women leaders as someone who is more outgoing, democratic, caring, artistic, be kind, careful and conscientious, compassionate and cautious. Therefore,image of women as a person who also has the leadership capacity can be revitalized to bring back the gait struggles women figure very inspiring leadership. Because, requirement for an educational leader is that the educational leader must be able to lead the organization/ institution, isresponsible for the achievement of the organization/ institution, is also expected to be leaders and innovators in organizations/ institutions. It also must have the leadership skills and human relations skills and good leadership to implement the model in accordance with the characteristicsof her, because the real success of an organization/ institution essentially lies in the efficiency and effectiveness of the appearance of a leader. Thus, in this case, both one’s biological factor that men and women are not the main requirements in educational leadership.Keyword: Women’s Leadership, Educational Leadership, Islamic Perspective